Inhibitory effects of Triphala on CYP isoforms in vitro and its pharmacokinetic interactions with phenacetin and midazolam in rats - Jannarin Nontakham (2022)
Context: Direct evidence of Triphala-drug interactions has not been provided to date. Objective: This study was aimed to determine the effects of Triphala on cytochrome P450 (CYP) isoforms and P-glycoprotein (P-gp) in vitro, and to investigate pharmacokinetic interactions of Triphala with CYP-probes in rats. Materials and methods: Effects of Triphala on the activities of CYP isoforms and P-gp were examined using human liver microsomes (HLMs) and Caco-2 cells, respectively. Pharmacokinetic interactions between Triphala and CYP-probes (i.e., phenacetin and midazolam) were further examined in rats. Results: Triphala extract inhibited the activities of CYP isoforms in the order of CYP1A2>3A4>2C9>2D6 with the IC50 values of 23.6 ± 9.2, 28.1 ± 9.8, 30.41 ± 16.7 and 93.9 ± 27.5 μg/mL, respectively in HLMs. It exhibited a non-competitive inhibition of CYP1A2 and 2C9 with the Ki values of 23.6 and 30.4 μg/mL, respectively, while its inhibition on CYP3A4 was competitive manner with the Ki values of 64.9 μg/mL. The inhibitory effects of Triphala on CYP1A2 and 3A4 were not time-dependent. Moreover, Triphala did not affect the P-gp activity in Caco-2 cells. Triphala, after its oral co-administration at 500 mg/kg, increased the bioavailabilities of phenacetin and midazolam by about 61.2% and 40.7%, respectively, in rats. Discussion and conclusions: Increases observed in the bioavailabilities of phenacetin and midazolam after oral co-administration of Triphala in rats provided a direct line of evidence to show Triphala-drug interactions via inhibition of CYP1A and CYP3A activities, respectively. These results, together with the lack of time-dependency of CYP 1A2 and 3A4 inhibition in vitro, suggested that the inhibitory effect of Triphala is primarily reversible.